Chekhovian Motifs, Imagery and Techniques in the Works of Russian Writers of the Turn of the 21st Century - Гордович, Кира (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The creative principles and techniques of Anton Chekhov have proved attractive to modern writers. Many late-20th-century authors, e.g. Tendryakov or Sasha Sokolov, used the naiveté and naturalness of a child’s mind when depicting contradictions and controversial issues. A connection with Chekhov is evident in the development of the theme of a mental institution, its doctors and patients (Makanin, Pelevin). Also the Chekhovian principle of refusal to categorically judge the words and deeds of the characters gains fundamental importance (Dovlatov). It is from Chekhov that modern writers have learnt to present serious psychological issues and world-view questions through commonplace imagery.